Uwagi o dramaturgii filmu dokumentalnego - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Comments on the Dramaturgy of Documentaries The paper aims at analyzing the relationship between dramaturgy in documentary film and fiction film as a form of storytelling governed by similar rules. The author tries to answer questions about the methods used to shape the material in documentary films. She presents an analysis of two Polish documentaries: Siberian Lesson and Argentinean Lesson by Wojciech Staroń. The structures of both works are based on the theme of the journey. These films represent a type of drama resulting from real-life events, close Kracauer’s theory of “the found story” and Kieślowski’s “dramaturgy of reality”. They also implement the basic assumptions of the paradigm (of the mythic structures) described by Joseph Campbell and Christopher Vogler typical of fiction films.